Penanaman nilai empati melalui aplikasi “Teman Disabilitas” di SD islamic leader school - Amanda Aulia Rahmatika; Syarip Hidayat; Muhammad Rijal Wahid Muharram (COLLASE (Creative of Learning Students Elementary Education), 2023)
This research is a research on the development of the â€œTeman Disabilitasâ€ application to instill the value of empathy for people with physical disabilities. The purpose of the research is to find out the need for applications based on the value of empathy for disability in elementary schools, develop and describe the form of application designs based on the value of empathy for disabilities in elementary schools, conduct trials of application products based on empathy values for disabilities in elementary schools, and produce a form of the end of the application product based on the value of empathy for disabilities in elementary schools. The method in this research is Design Based Research according to Reeves. This research was conducted at SD Islamic Leader School. The stages in this research are (1) principles and collaborative problem and practice analysis, (2) prototype development as a solution based on existing design, and technological innovations, (3) iterative testing cycle and solution refinement in practice, and (4) cycle improvement and refinement of solutions in practice. The types of data collection used are interviews, questionnaires, observations, and Values Clarification Test. The final product of this research is the â€œTeman Disabilitasâ€ application. This research trial was conducted before and before using the â€œTeman Disabilitasâ€ application using the Values Clarification Test. Based on data analysis, there was an increase in the empathy value of students before and before using the "Teman Disabilitas" application.Penelitian ini merupakan penelitian pengembangan aplikasi â€œTeman Disabilitasâ€ guna menanamkan nilai empati kepada disabilitas fisik. Tujuan dari penelitian yaitu untuk mengetahui kebutuhan aplikasi berbasis nilai empati terhadap disabilitas di Sekolah Dasar, mengembangkan dan mendeskripsikan bentuk rancanagan aplikasi berbasis nilai empati terhadap disabilitas di Sekolah Dasar, melakukan uji coba produk aplikasi berbasis nilai empati terhadap disabilitas di Sekolah Dasar, dan menghasilkan bentuk akhir produk aplikasi berbasis nilai empati terhadap disabilitas di Sekolah Dasar. Metode pada penelitian ini yaitu Design Based Reseacrh menurut Reeves. Penelitian ini dilakukan di SD Islamic Leader School. Adapun tahapan pada penelitian ini (1) identifikasi dan analisis masalah dan praktisi secara kolaboratif, (2) pengembangan prototype sebagai solusi yang berdasarkan desain, prinsip, dan inovasi teknologi yang ada, (3) siklus berulang pengujian dan penyempurnaan solusi dalam praktik, dan (4) siklus berulang pengujian dan penyempurnaan solusi dalam praktik. Jenis pengumpulan data yang digunakan yaitu wawancara, angket, observasi, dan Values Clarification Test. Produk akhir penelitian ini berupa aplikasi â€œTeman Disabilitasâ€. Uji coba penelitian ini dilakukan pada saat sesudah dan sebelum menggunakan aplikasi â€œTeman Disabilitasâ€ menggunakan Values Clarification Test. Berdasarkan analisis data adanya peningkatan nilai empati peserta didik pada saat sesudah dan sebelum menggunakan aplikasi â€œTeman Disabilitasâ€.